Chemical composition and antioxidant activities of essential oils from different parts of the oregano - Han, Fei (Zhejiang University Press, 2017)

(untitled) (J Zhejiang Univ Sci B)
This research was undertaken in order to characterize the chemical compositions and evaluate the antioxidant activities of essential oils obtained from different parts of the Origanum vulgare L. It is a medicinal plant used in traditional Chinese medicine for the treatment of heat stroke, fever, vomiting, acute gastroenteritis, and respiratory disorders. The chemical compositions of the three essential oils from different parts of the oregano (leaves-flowers, stems, and roots) were identified by gas chromatography-mass spectrometry (GC-MS). The antioxidant activity of each essential oil was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay and reducing the power test. Among the essential oils from different parts of the oregano, the leaf-flower oils have the best antioxidant activities, whereas the stem oils are the worst. The results of the DPPH free radical scavenging assay showed that the half maximal inhibitory concentration (IC50) values of the essential oils were (0.332±0.040) mg/ml (leaves-flowers), (0.357±0.031) mg/ml (roots), and (0.501±0.029) mg/ml (stems), respectively. Interestingly, the results of reducing the power test also revealed that when the concentration exceeded 1.25 mg/ml, the leaf-flower oils had the highest reducing power; however, the stem oils were the lowest.